The Foochow Chinese: Moving towards a pan-Chinese identity anchored to Mandarin - Ting, Su Hie; Ting, Su Lin (2020)
The study investigated the use of Mandarin and Chinese dialects, and attitudes towards these languages among the Foochow living in Sibu, Sarawak, Malaysia. The study involved 408 Foochow respondents (204 children, 204 parents). As most of the respondents’ close friends, neighbours and colleagues were Foochow, and Chinese in general, Foochow and Mandarin were the two main languages used, but English, Malay and Iban were sometimes used with people from other ethnic groups. More parents felt at ease speaking Foochow in all situations but more children felt that it is nothing special to speak their dialect. The most cherished and emotionally expressive language for the parents was Foochow but for their children, it was Mandarin. More parents were aware of cultural associations and activities than their children. They believed that the use of Chinese dialects will decrease in future and intergenerational transmission of the dialect is important. Yet they were still looking to cultural associations and the government to promote their culture and dialect. The study indicated that the markers for membership of their Chinese dialect group are ancestry, language, living among people from the same dialect group, cultural practices, and religion.